Multi-dimensional review of Myanmar. Vol. 1, Initial assessment - Organisation for Economic Co-operation and Development (OECD development pathways, ISSN 2308-734X, 2013)
Summary.
Keywords: taloudellinen kehitys; talouskasvu; taloudellinen kehitys : Myanmar; talouskasvu : Myanmar; kestävä kehitys : Myanmar; kehitysmaat : Myanmar